Enantioselective β-hydroxy thioesters formation via decarboxylative aldol reactions of malonic acid half thioesters with aldehydes promoted by chloramphenicol derived sulfonamides1. Issue 34 (24th August 2017) - Wang, Yafeng; Huang, Guanxin; Hu, Sha; Jin, Kaijun; Wu, Yan; Chen, Fener
Abstract: A highly enantioselective synthesis of chiral β -hydroxy thioesters that uses a decarboxylative aldol reaction of malonic acid half thioesters and aldehydes catalyzed by a chloramphenicol base-derived bifunctional organocatalyst is reported. The resulting chiral β -hydroxy thioesters were obtained in high yields (up to 82%) with good to excellent enantioselectivities (up to 94% ee). The synthetic application of the methodology is illustrated by the asymmetric synthesis of the selective serotonin reuptake inhibitor dapoxetine. Graphical abstract: